1989
DOI: 10.1159/000168002
|View full text |Cite
|
Sign up to set email alerts
|

Regular Analgesic Intake and the Risk of End-Stage Renal Failure

Abstract: The strength of the association between regular analgesic intake (RAI) and end-stage renal failure (EF) has been insufficiently established until now. A case-control study was conducted to estimate the relative risks (RR) of EF after RAI (defined as consumption of 15 or more analgesic doses per month for a continuous period of at least 1 year) for cumulative drug intake, single-ingredient analgesics, combinations, and specific compounds. The case group included all patients with EF undergoing renal replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 11 publications
3
65
0
3
Order By: Relevance
“…One such possible pathway is the shared ability of these drugs to induce renal damage leading to increased cell proliferation at the target site, a recognized mechanism of increased cancer risk in humans (Henderson et al, 1991). Aspirin, non-aspirin NSAID, phenacetin and acetaminophen used alone or in combination have been reported to be associated with chronic nephropathy, chronic renal failure or endstage renal disease in several case-control studies (Pommer et al, 1989;Sandler et al, 1989;Perneger et al, 1994). In vivo and in vitro rodent models have shown that aspirin, non-aspirin NSAID and acetaminophen undergo in situ metabolic activation in the kidney with subsequent covalent binding of the highly reactive metabolites to tissue/microsomal proteins, leading to tubular necrosis (Mitchell et al, 1977;McMurtry et al, 1978;Kyle and Kocsis, 1985;Emeigh Hart et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…One such possible pathway is the shared ability of these drugs to induce renal damage leading to increased cell proliferation at the target site, a recognized mechanism of increased cancer risk in humans (Henderson et al, 1991). Aspirin, non-aspirin NSAID, phenacetin and acetaminophen used alone or in combination have been reported to be associated with chronic nephropathy, chronic renal failure or endstage renal disease in several case-control studies (Pommer et al, 1989;Sandler et al, 1989;Perneger et al, 1994). In vivo and in vitro rodent models have shown that aspirin, non-aspirin NSAID and acetaminophen undergo in situ metabolic activation in the kidney with subsequent covalent binding of the highly reactive metabolites to tissue/microsomal proteins, leading to tubular necrosis (Mitchell et al, 1977;McMurtry et al, 1978;Kyle and Kocsis, 1985;Emeigh Hart et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies easily identify the adverse effects of long-term analgesic use or abuse (50,51,61,179,180,200,201). The diffuse symptoms, the protracted period of time over which the lesion develops, and the fact that it is difficult to gauge how much of which analgesic or NSAIDs was consumed over what period of time has precluded more detailed analysis of the epidemiolo$ical databases.…”
Section: Analgesic Nephropathymentioning
confidence: 99%
“…There are no indications as to whether there are risk factors that could predispose individuals to the lesion. While the role of coformulation of caffeine has been presented as a risk factor (36,95,98,179,180), there is no clear experimental (67,68,133,140) or epidemiological (48,152,153) evidence that this is so.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixtures often also contained caffeine. Interestingly, in some epidemiological studies caffeine content was the best predictor for subsequent renal failure (5,6). The renal medullary toxicity of these particular analgesic drugs was apparently supported by animal studies, but interpretation of both the epidemiological and animal studies has been questioned (7)(8)(9).…”
mentioning
confidence: 99%